2019
DOI: 10.3390/su11092689
|View full text |Cite
|
Sign up to set email alerts
|

Corporate–NGO Partnerships through Sustainability Labeling Schemes: Motives and Risks

Abstract: This article examines the development of partnerships between multinational companies (MNCs) and large nongovernmental organizations (NGOs) through voluntary product labeling schemes. First, the economics, management, and business literature are reviewed to highlight cross-checking, consistencies, and complementarities among these disciplines to identify and analyze the motives of partnering via voluntary product labeling. This analysis shows that, through such partnerships, companies and NGOs share similar ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 72 publications
2
20
0
2
Order By: Relevance
“…The study's findings also highlighted the importance of improving the financial stability of NPOs, with leveraging resources being the most important motives in most of the partnerships. Attracting private sector finance for infrastructure development is critical for economic and social development, improving environmental sustainability, reducing poverty and inequality, and ensuring decent work for all (SDG 9) [31]. Generally, it was concluded that SDG 17-Partnerships for the Goals, should empower NPOs to implement the other SDGs through collaboration with other actors, in order to create value for nature and society by sharing knowledge, expertise, technology, and financial resources [103].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The study's findings also highlighted the importance of improving the financial stability of NPOs, with leveraging resources being the most important motives in most of the partnerships. Attracting private sector finance for infrastructure development is critical for economic and social development, improving environmental sustainability, reducing poverty and inequality, and ensuring decent work for all (SDG 9) [31]. Generally, it was concluded that SDG 17-Partnerships for the Goals, should empower NPOs to implement the other SDGs through collaboration with other actors, in order to create value for nature and society by sharing knowledge, expertise, technology, and financial resources [103].…”
Section: Discussionmentioning
confidence: 99%
“…These organizations have networks along with knowledge, experience, skills, and resources in the societal issues that firms and other actors face. Therefore, for a more practical purpose, selecting the right partner and establishing a coordination committee between partners before a partnership engagement are absolutely critical steps to the success of a CSR strategy [31]. In this context, Fontana [106] identified the urgent need for an informed view of charitable organizations' expectations before initiating collaboration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study fills this gap and extends his study by highlighting a new perspective for the understanding of sustainability. This research principally attempts to bridge this gap by examining the understanding of SR, the barriers and the drivers in NGOs in order to support a framework of action for strong sustainability that preserves nature, promotes societal wellbeing and improves the quality of life by NGOs [12,15,59]. Accordingly, this research seeks to answer the following research questions: R1: What is the trend in SR in NGO This research makes several contributions to knowledge, aside from the fact that it enriches the existing literature on SR in NGOs, this research provides insight for theoretical blending and pluralism that supports greater research applicability or the development of 'indigenous' accounting theory.…”
Section: Introductionmentioning
confidence: 99%